Minat Mahasiswa Akuntansi Memperoleh Sertifikasi Chartered Accountant - Ananda, Andrea Diva; Ratnadi, Ni Made Dwi (E-Jurnal Akuntansi; Vol 31 No 9 (2021), 2021)
This research aimed to determine the factors affecting accounting students’ interest in obtaining the CA certification. The theory of planned behavior is used as a theoretical basis to explain the effect of attitudes toward behavior, subjective norms, and perceived behavioral control on the interest in obtaining CA certification. The level of knowledge is also one of the information factors that can influence behavior intention. The number of samples used in this study was 168 respondents to determine the sample, namely the simple random sampling method. Data were collected using a questionnaire. The analysis technique used is multiple linear regression analysis. The analysis results indicate that attitudes toward behavior, subjective norms, and perceived behavioral control positively affect accounting students’ interest to obtain CA certification. Meanwhile, the level of knowledge about CA does not affect accounting students’ interest to obtain CA certification. Keywords: Interest; Attitudes Toward Behavior; Subjective Norms; Perceived Behavioral Control; Knowledge.